Fen bilgisi öğretmenleri ve fen bilgisi öğretmen adaylarının değerler eğitimine yönelik görüşleri. - KARABULUT, Hilal; ALTINIŞIK, Yasemin; GÖKÇE, Hasan; KARİPER, İ. Afşin (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
This study aimed to examine the views of prospective teachers who graduated from science teaching and science teachers on values education. In this context, the phenomenology design, one of the qualitative research methods, was preferred. Prospective teachers who graduated from the science teaching program and teachers who have at least 10 years of experience in the field participated in the study. There are 6 volunteer teachers and 6 volunteer prospective teachers in the study group. A semistructured interview form was applied to the participants. After the semi-structured interview form prepared by the researcher was prepared, it was sent to three different field experts and feedback was requested from the researchers on the form. After the expert opinions, the necessary arrangements were made in the questions and the form took its final form. The obtained data were analyzed with content analysis. In the study, it was concluded that science teachers expressed values education with concepts such as love, respect and faith; while prospective teachers associated it with concepts such as morality, ethics and faith. Prospective teachers stated that values education to be processed in science education can provide respect and collaborative learning skills to teachers and students. It was also concluded that science teachers should have knowledge of values education. At the end of the study, it was suggested that all science teachers and teacher candidates in the field and in the education process should be made aware of values education.